การวิเคราะห์สภาพปัญหาที่เกิดขึ้นในโครงการก่อสร้างขนาดเล็ก - วิริยะ แสงสว่าง (จุฬาลงกรณ์มหาวิทยาลัย, 2006)
The research has of two important objectives. The first one is to study the problems occurring in small construction projects, either classified as public and private sectors or as road and building constructions. The second objective is to analyze and offer some initiative suggestions towards the problems in small construction projects. The problems in small construction projects were analyzed and collected by using the interviewing method with individuals having construction experience for a minimum of 5 years. Forty Samples of owners and contractors were interviewed, using face to face interviewing method with formal interview. The interviewer performed rated-scale interview and in-depth interview. The result revealed that the problems having the most impact and happening most frequently in small construction projects are unpredictable physical site, fluctuation along with lack of fluctuation provisions construction delay, incomplete documents and construction cost. In addition, suggestion were made to alleviate solve the problems: suitable contract provisions, application of construction management methods, monitoring of construction progress and information checking relevant to construction before as well as between the construction process, and a good coordination between those parties concerned to prevent and solve the problems